Design formulation of goat feedstock from palm kernel cake (PKC) - Mohd Shahrir, Baharuddin (2010)
The application of palm kernel cake (PKC) as the alternative feed has become crucially important for the livestock industry,yet the usage of PKC as the main protein sources has found the answer to the expensive price of the imported corn and soy meals.Several studies on the capability of PKC to substitute corn and soy meals as the main source of protein for the supplementary feed production has been done and the results obtained are positive.This research is aimed to formulate a supplementary goat feed using PKC and study the effect of the feed to the cost of production. There are three samples that are going to be formulated, as the ingredients for each sample are varies,especially the content of PKC and agricultural waste.The formulated supplementary goat feed is analyzed using Near Infrared Spectrometer (NIIR),where the protein,fiber,ash,energy and several nutrient contents can be fully determined. Meanwhile,Atomic Absorption Spectroscopy (AAS) is used to determine the composition of metals inside the feed.The results obtained shows that all samples producing results that are likely within the range of the typical nutrient requirement,according to the standard nutrient requirement for goats.However, sample two is most likely preferable to be commercialized as its use the maximum amount of PKC and agricultural waste,thus,in term of cost analysis,the cost of production for this sample is the lowest and this sample is highly commercialization.